2022
DOI: 10.1080/15476286.2021.2016203
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted functions of the Fat mass and Obesity-associated protein (FTO) in normal and cancer cells

Abstract: The last decade has seen mRNA modification emerge as a new layer of gene expression regulation. The Fat mass and obesity-associated protein (FTO) was the first identified eraser of N6-methyladenosine (m6A) adducts, the most widespread modification in eukaryotic messenger RNA. This discovery, of a reversible and dynamic RNA modification, aided by recent technological advances in RNA mass spectrometry and sequencing has led to the birth of the field of epitranscriptomics. FTO crystallized much of the attention o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 79 publications
0
17
0
Order By: Relevance
“…Liu et al reported that the knockdown of "writers" METTL3/METTL14 and "reader" YTHDF2 increased viral infection/replication, while the knockdown of "eraser" ALKBH5 decreased infection in human hepatocarcinoma (Huh7) cells after 72 hpi [802]. Their results were confirmed by Zannella et al who used rhein-an inhibitor of m 6 A "erasers"-to knockdown fat mass and obesity-associated protein (FTO) [809] in Vero cells infected by SARS-CoV-2, where a dose-dependent effect was seen after 14 hpi with interference of viral life cycle to complete blockage of infection at the highest dose used [810]. Conversely, works of others have found m 6 A "writers" and "readers" to positively regulate SARS-CoV-2 infection and replication, where their knockdowns decreased viral replication (Table 1, Figure 3).…”
Section: Is M 6 a A Positive Or Negative Regulator Of Sars-cov-2 Repl...mentioning
confidence: 92%
“…Liu et al reported that the knockdown of "writers" METTL3/METTL14 and "reader" YTHDF2 increased viral infection/replication, while the knockdown of "eraser" ALKBH5 decreased infection in human hepatocarcinoma (Huh7) cells after 72 hpi [802]. Their results were confirmed by Zannella et al who used rhein-an inhibitor of m 6 A "erasers"-to knockdown fat mass and obesity-associated protein (FTO) [809] in Vero cells infected by SARS-CoV-2, where a dose-dependent effect was seen after 14 hpi with interference of viral life cycle to complete blockage of infection at the highest dose used [810]. Conversely, works of others have found m 6 A "writers" and "readers" to positively regulate SARS-CoV-2 infection and replication, where their knockdowns decreased viral replication (Table 1, Figure 3).…”
Section: Is M 6 a A Positive Or Negative Regulator Of Sars-cov-2 Repl...mentioning
confidence: 92%
“…Currently, targeted therapies are the standard treatment options for renal cell carcinoma, functioning as an oncogene or anti-oncogene in malignant tumors ( Relier, Rivals & David, 2022 ; Yang et al, 2022 ). On this basis of epigenetics modification, this regulatory effects of IGF2BP1 suggested that m 6 A could be utilized to develop new strategies for targeted therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, targeted therapies are the standard treatment options for renal cell carcinoma, functioning as an oncogene or anti-oncogene in malignant tumors 21,22 . On this basis of epigenetics modi cation, this regulatory effects of IGF2BP1 suggested that m 6 A could be utilized to develop new strategies for targeted therapies.…”
Section: Discussionmentioning
confidence: 99%